คอนเสิร์ต“ปิตุภูมิในดวงใจ”: การสร้างสำนึกความเป็นชาตินิยมเวียดนามในบริบทสากล: Tổ Quốc Trong Tim Concert: The Construction of Vietnamese Nationalism in a Global Context - จันทะมาตย์ ปิติภัทร; จันทรานุสรณ์ แก้วตา (Journal of Humanities and Social Sciences (HUSOKKU), 2026)
The article “Tổ Quốc Trong Tim” Concert: The Construction of Vietnamese Nationalism in a Global Context” aims to examine the construction and transmission of nationalistic consciousness through musical performing arts in the national concert, Tổ Quốc Trong Tim (Fatherland in My Heart). This qualitative research employs content analysis and cultural interpretation specifically examining stage design, lyrical content, and audience participation to understand the symbolic communication that constructs the meaning of the nation in contemporary society. The study utilizes the "Third Space" conceptual framework proposed by Soja (1996) and Chayan Vaddhanaphuti (2006), integrated with the concept of "Ritual Space" by Kanjana Kaewthep (2017), to explain the relationships among physical space, social space, and mental space. The findings reveal that the concert functions as a cultural space connecting the past and the present, transmitting national ideology in a contemporary format, and providing a platform for the younger generation to participate in reinterpreting national identity within a new context. Therefore, the performance is not merely an artistic celebration but serves as a “cultural weapon” that cultivates national pride and consciousness, ensuring their persistence amidst globalization and the transitions of modern society.